Sir Arthur Conan Doyle’s Resignation from the Society for Psychical Research - Price, Leslie (Journal of Scientific Exploration, 2012)
Luca Gasperini's tribute to Bozzano is very welcome in "Ernesto Bozzano: An Italian Spiritualist and Psychical Researcher" in JSE 25:4 (Gasperini 2011). Bozzano's friendship with Conan Doyle would merit further exploration. As Gasperini notes, Conan Doyle resigned his membership in the Society for Psychical Research in 1930, though he was an ordinary dues-paying member and not an honorary member. He did not take with him 77 other members. The passage cited from Mauskopf and McVaugh (1980) does indeed say that six members and one associate resigned in support of Doyle, and that 77 others resigned in the year, but there is no reason to reject the statement made by the Society for Psychical Research in their annual report: "A great majority of those who gave any reason for their resignation mention financial stringency, long illness, residence abroad, etc." (Annual Report . . . 1931). Recent research, cited by Gasperini, has shown that the Millesimo phenomena which Sir Arthur defended in 1930 were even more doubtful than was suggested at the time (Biondi 2009). Doyle went on to resign angrily as president of a leading Spiritualist body (London Spiritualist Alliance) shortly before his death in July 1930 (Gaunt & Price 2006).